PENGARUH MANAJEMEN PENGETAHUAN, BUDAYA ORGANISASI TERHADAP KINERJA ORGANISASI - Rofikotul Arfati (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2017)
This study aims to examine and analyze the influence of knowledge management and organizational culture on organizational performance. This study uses theory of Resources Based View. The study conducted by the Agency for Assessment and Application of Technology (BPPT), with 62 respondents on engineering positions. Data collected using questionnaire method that is by giving list question or questionnaire which submitted directly to respondent and also by email. Data analysis techniques in this study using Partial Least Square (PLS) with WarpPLS 3.0. The results showed that knowledge management and organizational culture have positive and significant influence on organizational performance. Keywords : Knowledge Management, Organization Culture, Performance Organization